Preparation of Ti and Fe Composition Gradient Thin Films by Sputtering with Mixed Powder Targets - Satake, Takahiko; Kawasaki, Hiroharu; Aoqui, Shin-ichi (E-journal of surface science and nanotechnology, 2023)
A composition-controlled functional film preparation method by plasma process using powder mixture targets. Thin films of a mixture of titanium (Ti) and stainless steel (SUS), which is known as a metal that affords a high rate of hydrogen penetration, were prepared using mixture powder targets of titanium oxide (TiO2) and SUS in this study. Experimental results indicated that titanium and SUS mixture thin films were successfully prepared, and their mixtures could be controlled both on the SUS and Si substrate surface. In addition, the mixture of the TiO2 and SUS powders in the target strongly affects surface morphology and/or crystallinity in the produced functional thin film. Gradient-functional thin films were prepared using 11 powder targets with variable Ti and Fe compositions. X-ray photoelectron spectroscopy depth profile results suggest that the Ti and Fe composition gradient thin films can be prepared by sputtering with mixed powder targets.